An F-type lectin domain directs the activity of Streptosporangium roseum alpha-l-fucosidase. (30th August 2018) - Bishnoi, Ritika; Mahajan, Sonal; Ramya, T N C
Abstract: F-type lectins are phylogenetically widespread but selectively distributed fucose-binding lectins with L-fucose- and calcium-binding sequence motifs and an F-type lectin fold. Bacterial F-type lectin domains frequently occur in tandem with various protein domains in diverse architectures, indicating a possible role in directing enzyme activities or other biological functions to distinct fucosylated niches. Here, we report the biochemical characterization of a Streptosporangium roseum protein containing an F-type lectin domain in tandem with an NPCBM-associated domain and a family GH 29A alpha-l -fucosidase domain. We show that the F-type lectin domain of this protein recognizes fucosylated glycans in both α and β linkages but has high affinity for a Fuc-α-1, 2-Gal motif and that the alpha-l -fucosidase domain displays hydrolytic activity on glycan substrates with α1-2 and α1-4 linked fucose. We also show that the F-type lectin domain does not have any effect on the activity of the cis- positioned alpha-l -fucosidase domain with the synthetic substrate, 4-Methylumbelliferyl-alpha-l -fucopyranoside or on inhibition of this activity by l -fucose or deoxyfuconojirimycin hydrochloride. However, the F-type lectin domain together with the NPCBM-associated domain enhances the activity of the cis -positioned alpha-l -fucosidase domain for soluble fucosylated oligosaccharide substrates. While there are many reports of glycoside hydrolase activity towards insoluble and soluble polysaccharides being enhanced by cis -positioned carbohydrate binding modules on the polypeptide, this is the first report, to our knowledge, of enhancement of activity towards aqueous, freely diffusible, small oligosaccharides. We propose a model involving structural stabilization and a bind-and-jump action mediated by the F-type lectin domain to rationalize our findings.